Correlation between KLK6 expression and the clinicopathological features of glioma - Lou, Jiangtao; Si, Haiyan; Chen, Yingjian; Sun, Xiaoming; Zhang, Hua; Niu, Aijun; Hu, Chengjin (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: We measured the impact of changing KLK6 expression levels on the pathological grade of gliomas and on proliferation rate, cell cycle progression, and apoptosis in the U251 glioblastoma cell line. Material and methods : The expression of KLK6 in 35 brain glioma tissues and adjacent noncancerous tissues was measured using real-time quantitative polymerase chain reaction (PCR) and the relationship between KLK6 expression and pathological grades was analysed. Results: The KLK6 expression in U251 cells was silenced by a specific siRNA, and the effects on proliferation, the cell cycle, and apoptosis were compared to wild type cells. Expression of KLK6 was downregulated in gliomas relative to matched noncancerous tissue. There was no obvious relationship between patient sex, pathological grade, or tumour classification and the expression of KLK6. In the U251 cell line, cell proliferation was enhanced and the fractions of cells in the G2 and S phases were increased by siRNA-mediated KLK6 silencing. Conclusions : Expression of KLK6 inhibits tumour growth. Decreased KLK6 expression may be a possible risk factor for glioma.